Stability of Charge - Trivedi, Nripesh (International Journal of Scientific Research and Management (IJSRM), 2024)
Electricity is fire as electricity produces heat and light which are the properties of fire. Electricity has charge. Thus, charge is also fire or fire is charge. Stability of charge is given by temperature. This could be verified from applications in daily life such as making of bricks at high temperature, storage of heated water in thermos flask or simply for keeping the fire burning one needs temperature. Thus, it could be seen that stability of charge is given by temperature since fire is charge (as described above).As shown in [1] source of fire is mass, thus temperature could be used to make strong and stable mass since stability of charge contained inside the mass is temperature.